Magnetic Optic Disks - Das, B.K.; Rastogi, A.C.; Kotnala, R.K. (DESIDOC Journal of Library & Information Technology, 2002)
Though the complexity of applications of information technology in various fields has grown, the consumer is demanding to process ever larger volumes of data. Magneto Optic Disk (MOD) technology is found to be the strongest candidate for supplementing if not replacing magnetic media for secondary removable storage in view of its low /cost and large storage density (Figure 1 and Table 1). Though large scale production (and hence its low cost) is yet to take place, it is bound to do so by 2000 AD given the expansion rate of production and market penetration of magneto-optic recording. Schroff and Chakravarti had studied in detail the technologies and applications of optical memories (1)The present study addresses the advances which have taken place in the last two years specifically in magneto-optic disks. http://dx.doi.org/10.14429/dbit.14.1.3090